A bibliometric analysis of global research trends in political literacy using web of science database / Nursyahida Zulkifli - Zulkifli, Nursyahida (Universiti Teknologi MARA Cawangan Pahang, 2021)
The objective of this study is to provide a bibliometric analysis on political literacy using one of the indexed journal databases which are Web of Science (WOS). This study analyzed the development trend and literature published in the study field of political literacy. The citation, bibliographical, and author keywords information of the related articles were exported to VOSviewer. The VOSviewer was used for the analysis that involved 122 documents related to political literacy studies. The findings showed that increasing trends of publications related to political literacy globally especially after 2007. Most of the documents of political literacy published in the WOS database between 1979 and 2021 were original research articles, which were mainly written in English. The findings of the present study are hoped to provide useful insights and information for the researchers to determine future directions related to the field of political literacy studies